Ultra-rapid VOCs sensors based on sparked-In2O3sensing films - K. Inyawilert (2018)
The volatile-organic-compounds (VOCs) sensors based on In2O3sensing film were successfully produced by a simple and cost-effective sparking process in a single step. Two indium wires were sparked and scanned repeatedly above Al2O3substrates equipped with Au interdigitated electrodes for 10-200 cycles at a high sparking voltage of 4.5 kV under atmospheric conditions. The functional nanoparticles and sensing film were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. The sensor response and response time of sensing films were systematically characterized toward ethanol (50-1000 ppm) and acetone (100-2000 ppm) with varying number of sparking cycles at 200-350 C in dry air. The relationship between sensing characteristics and the number of sparking cycles was extensively discussed based on the concept of diffusivity and reactivity of gases inside the oxide films. It was found that the sensing film had well-developed porous structures when the number of sparking cycles was not larger than 100 and the film became denser due to particle agglomeration and grain growth at higher numbers of sparking cycles, leading to deteriorated gas-sensing response. The In2O3sensing film produced with 100 sparking cycles exhibited the highest sensor response and ultra-high detection speed with very short response time of less than a second at an operating temperature of 350 C. In addition, the sensor response linearly increased and the response time decreased with increasing gas concentration. Moreover, sensors were highly sensitive to VOCs at low concentrations in the same range as the detection limit of human breath analyzer. Therefore, the sensor is a promising candidate as an ethanol and acetone detectors for drunken driving detection and diabetes diagnosis. © 2013 Elsevier B.V.